Pelatihan Kewirausahaan Bagi Wirausaha Pemula di Kota Pekalongan - Mahirun, Mahirun; Jannati, Arih; Prasetiani, Titi Rahayu; Tsamara, Tsamara (Universitas Pahlawan Tuanku Tambusai, 2023)
Entrepreneurship training for budding entrepreneurs in Pekalongan City is an effort to develop MSMEs to be competitive with other existing and developed businesses. The Department of Trade, Cooperatives and Small and Medium Enterprises of Pekalongan City in collaboration with the Faculty of Economics and Business, Pekalongan University conducted training activities aimed at fostering an entrepreneurial spirit and increasing sales of goods and services produced by MSMEs. The method used is entrepreneurship and marketing mix training for 60 (sixty) budding entrepreneurs in Pekalongan City. The types of activities that will be carried out in this series of PKM activities include: (1) Identification and determination of target participants; (2) Identification of needs; (3) Implementation of training, and (4) Evaluation of activities. The results of the PKM implementation are the implementation of activities at the Dafam Hotel with 60 participants from novice entrepreneurs in Pekalongan City. The first day was filled with exposure to Pekalongan City Government policies that support entrepreneurship. The second day was filled with entrepreneurial motivation material, and the third day was the presentation of marketing mix material.